Analisis Perencanaan Kebutuhan Bahan Baku Menggunakan Metode MRP pada Produksi Kursi Anyaman Aluminium (Studi Kasus : PT. XYZ) - Fani Nafianti Putri Farenzy; Sajiyo Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ operates in the furniture production sector using a Make-to-Order (MTO) system for woven aluminum chairs. The company's primary challenge lies in the unplanned management of material requirements, which often results in a mismatch between inventory levels and production process requirements. This situation necessitates the implementation of a raw material planning method that can improve inventory control effectiveness and maintain smooth production activities. This study utilized several analytical stages: demand forecasting, preparation of a Master Production Schedule (JIP), application of Material Requirement Planning (MRP), and analysis of lot sizing techniques using the Lot for Lot (LFL) and Period Order Quantity (POQ) methods. Based on the forecasting test results, the Moving Average method provided the smallest error value with a MAD of 70.37, thus being selected as the basis for JIP preparation. Furthermore, the MRP calculation results indicated that the LFL method resulted in an inventory cost of Rp32,875,500 and was deemed more optimal than the POQ method for raw material inventory control. The implementation of this method is expected to improve inventory efficiency while supporting the company's smooth production process.